PENGARUH KUALITAS PELAYANAN PENDIDIKAN TERHADAP KEPUASAN PELAJAR DI SMK TI AIRLANGGA SAMARINDA - Ferdy Arianto Haryadi (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The study aimed to identify and analyze the significance of quality of services concerning student satisfaction in endure of educated at SMK TI airlangga samarinda school as simultaneously and partial. Variables used in this research the independent variable consist of tangible (x1), reliability (x2), responsiveness (x3), assurance (x4), empathy (x5), and the dependent variable student satisfaction (y). Type research data analysis quantitatively is a data collection through research literature, the field, supporting documents, and questionnaires. Methods used to sampling is proposive method of sampling. With using formulas slovin, the total sample necessary as 74 respondents from the population, as many as 283 students then technique data analysis use double anlysis regression. This research result indicates that the impact of the quality of services, consist of tangible, reliability, responsiveness, assurance and empathy simultaneously. Have significant influence on the partial test (t) we can see that only variable responsiveness have significant impact on student satisfaction, and in the dominant or the result that responsiveness have more influence toward students satisfaction on airlangga school. Advice should be for vocational smk ti airlangga samarinda to increase quality of service which consist of tangible, reliability, assurance, and empathy and protecting even improve the responsiveness of their own that would give satisfaction felt by student.